2021
DOI: 10.1039/d1ce00722j
|View full text |Cite
|
Sign up to set email alerts
|

Selective alkane co-inclusion by methylene- and adamantane-bridged macrocycle with biphenyl units

Abstract: A methylene- and adamantane-bridged macrocycle with biphenyl units showed selective co-inclusion of n-hexane among the hexane isomers through crystallization. In the use of n-pentane or n-heptane, inclusion crystals with alkanes were not formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…6a). 35 We found that macrocycle (4) had a nearly rhombic structure with a cavity, in which dichloromethanes as crystallization solvent were contained by means of C-H⋯π and C-H⋯O interactions between the hydrogen atoms of the dichloromethanes and the biphenyl units or the oxygen atoms of the methoxy groups. The use of dibromomethane instead of dichloromethane resulted in the formation of crystal 4a.…”
Section: Resultsmentioning
confidence: 91%
“…6a). 35 We found that macrocycle (4) had a nearly rhombic structure with a cavity, in which dichloromethanes as crystallization solvent were contained by means of C-H⋯π and C-H⋯O interactions between the hydrogen atoms of the dichloromethanes and the biphenyl units or the oxygen atoms of the methoxy groups. The use of dibromomethane instead of dichloromethane resulted in the formation of crystal 4a.…”
Section: Resultsmentioning
confidence: 91%